Method for preparing ZnO-based voltage-sensitive ceramic by annealing enhanced low-temperature sintering

Through annealing, the low-temperature sintering process is enhanced, and problems such as insufficient cold sintering density and excessive grain growth in traditional high-temperature sintering are solved, and ZnO-based pressure-sensitive ceramic materials with high density and excellent mechanical properties are prepared.

CN119751043APending Publication Date: 2025-04-04CHONGQING UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411946765.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Cold sintering technology has shortcomings in improving the mechanical properties of ceramic materials, especially in terms of density and mechanical properties. Traditional high-temperature solid-phase sintering processes have problems of excessive grain growth and dopant volatility.

Method used

Annealing-enhanced low-temperature sintering process is adopted, and cold sintering is performed at a low temperature of 300°C and then annealing treatment is performed at an annealing temperature of 650°C-800°C to promote the sufficient reaction of the dopants at the grain boundary, form a stable intergranular phase, fill pores and enhance grain boundary binding force.

Benefits of technology

It significantly improves the density and mechanical properties of ceramics, with a relative density of 99.5%, an elastic modulus of up to 134GPa, and a Vickers hardness of more than 280HV, surpassing the performance of commercial resistor plates and having significant energy saving advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751043A_ABST
    Figure CN119751043A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing ZnO-based voltage-sensitive ceramic by annealing enhanced low-temperature sintering. The method comprises the following steps: preparing a formic acid solution from deionized water and glacial formic acid; mixing the initial ZnO powder with a metal oxide dopant to form a precursor powder; mixing the precursor powder with a formic acid solution, grinding and dispersing to obtain mixed slurry, putting the mixed slurry into a steel mold, and pressing for cold sintering; and annealing the sample subjected to cold sintering to finally obtain the high-performance ZnO-based voltage-sensitive ceramic. According to the invention, the process of annealing assisted cold sintering is adopted, so that more excellent mechanical properties can be obtained under a low-temperature condition, and the elasticity modulus reaches up to 134 GPa and the Vickers hardness exceeds 280 HV. The preparation method is suitable for being applied to high-performance electronic components, energy consumption is reduced, and the mechanical property of the ceramic is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing ZnO ceramics, and in particular to a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering. Technical Background

[0002] As an emerging low-temperature sintering method, cold sintering technology has shown significant advantages in energy consumption and nanocrystal control, but it has obvious shortcomings in improving the mechanical properties of ceramic materials. From a mechanistic analysis, during the cold sintering process, due to the low temperature (usually ≤300℃), the diffusion and rearrangement between particles are insufficient, resulting in more pores and discontinuous grain boundaries during the initial densification of the ceramic, resulting in more defects inside the material. Such pores and discontinuous grain boundaries weaken the mechanical properties of the material, especially the poor elastic modulus and hardness. In addition, it is difficult to form an effective intergranular phase during the cold sintering process, especially for complex multi-component systems. Low temperature makes it difficult for additives such as Bi2O3 and Y2O3 to react fully in the ZnO matrix, resulting in the grain boundary region often being amorphous. The presence of this amorphous phase will further weaken the overall strength of the ceramic, because the mechanical strength of the amorphous phase is much lower than that of the crystalline phase, which makes it easy for the cold sintered ceramics to produce local stress concentration, cracking or damage during use.

[0003] Although the traditional high-temperature solid-phase sintering process can greatly improve the density and mechanical properties of ceramics by promoting the diffusion of particles and the growth of grains in a high-temperature environment above 1100°C, it also has significant disadvantages. During the high-temperature solid-phase sintering process, excessive growth of grains is an inevitable phenomenon, which not only leads to uneven grain size inside the material, but also easily forms large grain areas, resulting in local stress concentration effects and reduced material toughness. In addition, the key dopant Bi2O3 is volatile above 825°C. Under the high-temperature conditions of the traditional solid-phase method, excessive volatilization of Bi2O3 will lead to a decrease in doping efficiency and affect the formation of intergranular phases, affecting the final material performance stability. More importantly, the excessively grown grains at high temperatures reduce the specific surface area of ​​the grain boundaries and weaken the ability of the grain boundaries to resist external stress, making it difficult for the hardness and elastic modulus of ceramic materials prepared by high-temperature solid-phase sintering to reach the optimal state. Therefore, although traditional solid-phase sintering can effectively improve the density of ceramics, its improvement in mechanical properties is limited.

[0004] These deficiencies have been significantly improved through the annealing-assisted cold sintering process. On the basis of cold sintering, through the subsequent annealing process (650℃-800℃), Bi2O3 and Y2O3 and other components further react at the grain boundaries to form a stable Bi3YO6 intergranular phase. The formation of this intergranular phase effectively fills the pores left over from the cold sintering process and significantly improves the density of the ceramic. Annealing also promotes further rearrangement and diffusion of particles, enhances the bonding force of grain boundaries, and makes the microstructure of the ceramic more uniform and stable. In addition, the annealing process eliminates the amorphous phase formed during cold sintering and replaces it with a high-strength intergranular phase structure, which significantly improves the mechanical properties of the material. This two-stage process that combines low-temperature energy saving with high-temperature microstructure optimization not only solves the problem of insufficient density of cold sintering, but also overcomes the unfavorable factors such as grain growth and volatilization of dopants during traditional high-temperature sintering, providing a preparation path for high-strength ZnO-based ceramics. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, which can prepare ZnO-based varistor ceramic materials with a relative density of up to 99.5% and excellent mechanical properties (elastic modulus up to 134GPa, Vickers hardness up to 277HV) under the condition of not exceeding 800°C. Compared with the sintering temperature of up to 1100°C in traditional high-temperature sintering, the method of the present invention not only has significant advantages in energy saving and emission reduction, but also can significantly improve the mechanical properties of ceramics, surpassing the performance of general commercial resistors.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the method comprising the following steps:

[0007] S1: Prepare a formic acid solution with deionized water and glacial formic acid, wherein the formic acid concentration is 1-5 mol%.

[0008] S2: Mixing the initial ZnO powder with a metal oxide dopant to form a precursor powder, wherein the metal oxide dopant accounts for 0-7.5 mol% of the total mass of the initial ZnO powder.

[0009] S3: the precursor powder prepared in S2 is mixed with the formic acid solution, and a mixed slurry is obtained after grinding and dispersion, wherein the amount of the citric acid solution added is 10-50wt% of the mass of the precursor powder.

[0010] S4: Put the mixed slurry into a steel mold, apply a pressure of 100-500 MPa, and cold sinter at 200-300°C for 0.5-3 hours.

[0011] S5: annealing the cold-sintered sample at a temperature ranging from 650 to 800° C. for a holding time of 4 to 10 h, and finally obtaining a ZnO-based varistor ceramic.

[0012] As an improvement, the metal oxide dopant is one or more of Bi2O3, Co2O3, Cr2O3, and Y2O3.

[0013] As an improvement, when the metal oxide dopant is composed of multiple metal oxides, each metal oxide accounts for 0.3-3 mol % of the total mass of the initial ZnO powder.

[0014] Compared with the prior art, the present invention has at least the following advantages:

[0015] (1) The annealing enhanced low-temperature sintering process proposed in the present invention significantly reduces the sintering temperature, which can save a lot of energy compared to traditional high-temperature sintering (1100°C and above). The process operation is simple, suitable for industrial large-scale production, and has significant economic and environmental benefits.

[0016] (2) The cold sintering combined with annealing process solves the common problems of high porosity and grain boundary discontinuity in the cold sintering process. The subsequent annealing promotes the full reaction of dopants (such as Bi2O3, Y2O3, etc.) at the grain boundary to form a stable intergranular phase, effectively eliminates the residual amorphous phase and micropores, and significantly improves the microstructural stability and strength of the material.

[0017] (3) This process avoids the abnormal growth of grains in traditional high-temperature sintering, promotes the homogenization of grain size, and significantly improves the densification of the material. The relative density of the ZnO-based varistor ceramic material finally prepared can reach more than 99.5%, and the porosity is significantly reduced, which makes the material have higher compressive strength.

[0018] (4) The innovative process of the present invention greatly improves the mechanical properties of ZnO-based varistor ceramics, with an elastic modulus of up to 134 GPa and a Vickers hardness of over 280 HV. The high hardness and high strength of the ceramic material enable it to maintain excellent stability and durability under harsh environments and high mechanical stress conditions, showing a wide range of industrial application prospects.

[0019] (5) The present invention converts the amorphous phase accumulated at the grain boundary after cold sintering into the Bi3YO6 intergranular phase. Compared with the amorphous phase generated after single cold sintering, the intergranular phase has higher hardness. In addition, the Bi3YO6 intergranular phase can not only effectively connect the adjacent loose grains, but also fill the pores formed during the cold sintering process, thereby significantly improving the relative density of the ceramic to 99.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1Grain morphology under different annealing temperature conditions.

[0021] Figure 2 The average grain size and relative density under different annealing temperature conditions.

[0022] Figure 3 XRD phase identification before and after different annealing.

[0023] Figure 4 Nanoindentation depths of samples with different annealing temperatures under the same load.

[0024] Figure 5 is the elastic modulus of samples at different annealing temperatures. DETAILED DESCRIPTION

[0025] The present invention is described in further detail below.

[0026] The present invention proposes an annealing enhanced low-temperature sintering process for preparing ZnO-based varistor ceramic materials with high density and excellent mechanical properties. Cold sintering, as a low-temperature sintering method, has advantages in energy conservation and emission reduction and nanocrystal control, but it is insufficient in improving mechanical properties, mainly because the cold sintering temperature is relatively low (≤300°C), which makes it difficult to achieve sufficient particle diffusion and grain boundary optimization, resulting in limited density and mechanical properties of the material. Therefore, the present invention combines cold sintering with annealing processes, by preliminarily densifying the ceramic at a low temperature of 300°C, and then annealing at 650°C to 800°C to promote intergranular phase formation, particle diffusion and grain boundary optimization, significantly improving the overall density and mechanical properties of the material.

[0027] The core of this process is that the initial cold sintering realizes the uniform dispersion of particles and the "dissolution-precipitation" mechanism through local wetting. However, in order to overcome the problem of pores and amorphous phase formation during cold sintering, the subsequent annealing effectively fills the pores and promotes dopants such as Bi2O3 and Y2O3 to form a stable Bi3YO6 intergranular phase at the grain boundary, further enhancing the structural density and strength of the ceramic. Through this two-stage process, the ZnO-based varistor ceramic prepared by the present invention has a relative density of 99.5%, an elastic modulus of 134GPa, and a Vickers hardness of 277HV, which exceeds the performance of existing commercial resistor products and has significant energy-saving advantages.

[0028] Example 1, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0029] (1) Prepare a 1 mol% formic acid solution using deionized water and glacial formic acid.

[0030] (2) Low temperature sintering step: Pure ZnO powder was mixed with 10 wt % formic acid solution, and a mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 100 MPa was applied, and cold sintering was performed at 300° C. for 1 hour.

[0031] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 650°C at a heating rate of 1°C / min and kept at this temperature for 4 hours to obtain a high-density ZnO ceramic, namely, Sample 1.

[0032] Example 2, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0033] (1) Prepare a 3 mol % formic acid solution using deionized water and glacial formic acid.

[0034] (2) Low temperature sintering step: Pure ZnO powder was mixed with 20 wt % formic acid solution, and a mixed slurry was obtained after grinding and dispersion. The mixed slurry was then placed in a steel mold, a pressure of 200 MPa was applied, and cold sintering was performed at 300° C. for 2 hours.

[0035] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 700°C at a heating rate of 3°C / min and kept at this temperature for 4 hours to obtain a high-density ZnO ceramic, namely, Sample 2.

[0036] Example 3, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0037] (1) Prepare a 3 mol % formic acid solution using deionized water and glacial formic acid.

[0038] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 3 mol% Bi2O3 and 0.3 mol% Cr2O3 to prepare a precursor powder, and mixed with 40 wt% formic acid solution. After grinding and dispersion, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 300 MPa is applied, and cold sintering is performed at 300°C for 2 hours.

[0039] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 750°C at a heating rate of 5°C / min and kept at this temperature for 5 hours to obtain a high-density ZnO ceramic, namely, Sample 3.

[0040] Example 4, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0041] (1) Prepare a 4 mol % formic acid solution using deionized water and glacial formic acid.

[0042] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 2 mol% Bi2O3 and 1 mol% Cr2O3 to prepare a precursor powder, and mixed with 40 wt% formic acid solution. After grinding and dispersion, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 400 MPa is applied, and cold sintering is performed at 300°C for 2 hours.

[0043] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 650°C at a heating rate of 7°C / min and kept at this temperature for 5 hours to obtain a high-density ZnO ceramic, namely, Sample 4.

[0044] Example 5, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0045] (1) Prepare a 4 mol % formic acid solution using deionized water and glacial formic acid.

[0046] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 2 mol% Bi2O3 and 2 mol% Co2O3 to prepare a precursor powder, and mixed with 50 wt% formic acid solution. The mixed slurry is obtained after grinding and dispersion. The mixed slurry is then placed in a steel mold, a pressure of 500 MPa is applied, and cold sintering is performed at 250°C for 3 hours.

[0047] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 800°C at a heating rate of 5°C / min and kept at this temperature for 7 hours to obtain a high-density ZnO ceramic, namely, Sample 5.

[0048] Example 6, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0049] (1) Prepare a 4 mol % formic acid solution using deionized water and glacial formic acid.

[0050] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 1.5 mol% Bi2O3, 2 mol% Cr2O3, 1 mol% Co2O3, and 3 mol% Y2O3 to prepare a precursor powder, and mixed with 20 wt% formic acid solution. The mixed slurry is obtained after grinding and dispersion. The mixed slurry is then placed in a steel mold, a pressure of 300 MPa is applied, and cold sintering is performed at 250°C for 3 hours.

[0051] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 650°C at a heating rate of 3°C / min and kept at this temperature for 4 hours to obtain a high-density ZnO ceramic, namely, Sample 6.

[0052] Example 7, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0053] (1) Prepare a 5 mol % formic acid solution using deionized water and glacial formic acid.

[0054] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 0.3 mol% Bi2O3, 0.3 mol% Cr2O3, 0.3 mol% Co2O3, and 2 mol% Y2O3 to prepare a precursor powder, and mixed with 20 wt% formic acid solution. After grinding and dispersion, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 300 MPa is applied, and cold sintering is performed at 250°C for 3 hours.

[0055] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 700°C at a heating rate of 5°C / min and kept at this temperature for 5 hours to obtain a high-density ZnO ceramic, namely, Sample 7.

[0056] Example 8, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0057] (1) Prepare a 5 mol % formic acid solution using deionized water and glacial formic acid.

[0058] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 3 mol% Bi2O3, 1 mol% Cr2O3, 1 mol% Co2O3, and 0.3 mol% Y2O3 to prepare a precursor powder, and mixed with 20 wt% formic acid solution. After grinding and dispersion, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 300 MPa is applied, and cold sintering is performed at 300°C for 1 hour.

[0059] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 770°C at a heating rate of 7°C / min and kept at this temperature for 6 hours to obtain a high-density ZnO ceramic, namely, Sample 8.

[0060] Example 9, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0061] (1) Prepare a 5 mol % formic acid solution using deionized water and glacial formic acid.

[0062] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 1 mol% Bi2O3, 1 mol% Cr2O3, 3 mol% Co2O3, and 1.5 mol% Y2O3 to prepare a precursor powder, and mixed with 30 wt% formic acid solution. After grinding and dispersion, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 300 MPa is applied, and cold sintering is performed at 300°C for 1 hour.

[0063] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 800°C at a heating rate of 10°C / min and kept at this temperature for 6 hours to obtain a high-density ZnO ceramic, namely, Sample 9.

[0064] Example 10, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0065] (1) Prepare a 4 mol % formic acid solution using deionized water and glacial formic acid.

[0066] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 1 mol% Bi2O3, 3 mol% Cr2O3, 1 mol% Co2O3, and 1.5 mol% Y2O3 to prepare a precursor powder, and mixed with 50 wt% formic acid solution. The mixed slurry is obtained after grinding and dispersion. The mixed slurry is then placed in a steel mold, a pressure of 400 MPa is applied, and cold sintering is performed at 200°C for 0.5 hours.

[0067] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 670°C at a heating rate of 1°C / min and kept at this temperature for 7 hours to obtain a high-density ZnO ceramic, namely, Sample 10.

[0068] Example 11, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0069] (1) Prepare a 4 mol % formic acid solution using deionized water and glacial formic acid.

[0070] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 3 mol% Bi2O3, 1 mol% Cr2O3, 1 mol% Co2O3, and 1.5 mol% Y2O3 to prepare a precursor powder, which is then ground and dispersed to obtain a mixed slurry. The mixed slurry is then placed in a steel mold, a pressure of 500 MPa is applied, and cold sintering is performed at 200°C for 1 hour.

[0071] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 770°C at a heating rate of 5°C / min and kept at this temperature for 8 hours to obtain a high-density ZnO ceramic, namely, Sample 11.

[0072] Example 12, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0073] (1) Prepare a 4 mol % formic acid solution using deionized water and glacial formic acid.

[0074] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 2 mol% Cr2O3 and 2 mol% Co2O3 to prepare a precursor powder, and then mixed with 30 wt% formic acid solution. The mixed slurry is obtained after grinding and dispersion. The mixed slurry is then placed in a steel mold, a pressure of 250 MPa is applied, and cold sintering is performed at 250°C for 1 hour.

[0075] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 800°C at a heating rate of 7°C / min and kept at this temperature for 9 hours to obtain a high-density ZnO ceramic, namely, Sample 12.

[0076] Example 13, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0077] (1) Prepare a 4 mol % formic acid solution using deionized water and glacial formic acid.

[0078] (2) Low-temperature sintering step: The ZnO initial powder was mixed with 3 mol% Bi2O3 to prepare a precursor powder, and then mixed with 30 wt% formic acid solution. After grinding and dispersion, a mixed slurry was obtained. The mixed slurry was then placed in a steel mold, a pressure of 350 MPa was applied, and cold sintering was performed at 250°C for 2.5 hours.

[0079] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 650°C at a heating rate of 3°C / min and kept at this temperature for 7 hours to obtain a high-density ZnO ceramic, namely, Sample 13.

[0080] Example 14, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0081] (1) Prepare a 4 mol % formic acid solution using deionized water and glacial formic acid.

[0082] (2) Low-temperature sintering step: The ZnO initial powder was mixed with 3 mol% Y2O3 to prepare a precursor powder, and then mixed with 40 wt% formic acid solution. After grinding and dispersion, a mixed slurry was obtained. The mixed slurry was then placed in a steel mold, a pressure of 300 MPa was applied, and cold sintering was performed at 300°C for 1 hour.

[0083] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 720°C at a heating rate of 5°C / min and kept at this temperature for 10 hours to obtain a high-density ZnO ceramic, namely, sample 14.

[0084] Example 15, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0085] (1) Prepare a 4 mol % formic acid solution using deionized water and glacial formic acid.

[0086] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 3 mol% Cr2O3 and 3 mol% Y2O3 to prepare a precursor powder, and mixed with 50 wt% formic acid solution. The mixed slurry is obtained after grinding and dispersion. The mixed slurry is then placed in a steel mold, a pressure of 300 MPa is applied, and cold sintering is performed at 300°C for 1 hour.

[0087] (3) Annealing assistance: The cold sintered sample was transferred into a muffle furnace and heated to 770°C at a heating rate of 7°C / min and kept at this temperature for 8 hours to obtain a high-density ZnO ceramic, namely, Sample 15.

[0088] Example 16, a method for preparing ZnO-based varistor ceramics by annealing enhanced low-temperature sintering, the process steps of which include:

[0089] (1) Prepare a 4 mol % formic acid solution using deionized water and glacial formic acid.

[0090] (2) Low-temperature sintering step: The ZnO initial powder is mixed with 3 mol% Bi2O3 and 1.5 mol% Y2O3 to prepare a precursor powder, and mixed with 30 wt% formic acid solution. After grinding and dispersion, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 300 MPa is applied, and cold sintering is performed at 300°C for 1 hour.

[0091] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 800°C at a heating rate of 10°C / min and kept at this temperature for 10 hours to obtain a high-density ZnO ceramic, namely, Sample 16.

[0092] The performance tests were carried out on the ZnO-based varistor ceramic samples prepared in some embodiments:

[0093] Figure 1Comparison of the grain morphology of the single cold sintered sample and the 900℃ annealed sample shows that a large amount of amorphous phases are accumulated at the grain boundaries of the single cold sintered sample. These amorphous phases are a large amount of unreacted dopants and the product of the "dissolution-precipitation" process of cold sintering. These amorphous phases are loose and do not completely fill the pores, thus causing serious deterioration in the density and mechanical properties of the ceramics. The sample annealed at 800℃ obviously eliminated the amorphous phases left over from the cold sintering, and converted them into secondary phases and filled them at the grain boundaries, greatly improving the density of the ceramics. This can be seen from Figure 3 It can be seen from the XRD pattern that the β-Bi2O3 present in the cold sintering is transformed into the Bi3YO6 intergranular phase after annealing. Figure 2 The average grain size and relative density of some annealed samples show that annealing can significantly enhance the density of ceramics. Combined with the performance statistics in Table 1, it can be found that annealing significantly enhances the elastic modulus and Vickers hardness of ZnO ceramics by optimizing density. The elastic modulus can reach 134GPa, and the corresponding Vickers hardness is 277HV, which exceeds the general commercial application level. Figure 4 The nanoindentation depth of some annealed samples under the same load. It can be seen that the annealed samples have a smaller indentation depth than the cold sintered samples, showing better mechanical strength. Figure 5 is the calculated elastic modulus value.

[0094] Table 1 shows the properties of the samples obtained in Examples 1-16

[0095]

Claims

1. A method for preparing ZnO-based varistor ceramics by annealing enhanced low temperature sintering, characterized in that: The method comprises the following steps: S1: preparing a formic acid solution with deionized water and glacial formic acid, wherein the formic acid concentration is 1-5 mol%; S2: mixing the initial ZnO powder with a metal oxide dopant to form a precursor powder, wherein the metal oxide dopant accounts for 0-7.5 mol% of the total mass of the initial ZnO powder; S3: mixing the precursor powder prepared in S2 with the formic acid solution, grinding and dispersing to obtain a mixed slurry, wherein the amount of the citric acid solution added is 10-50wt% of the mass of the precursor powder; S4: putting the mixed slurry into a steel mold, applying a pressure of 100-500 MPa, cold sintering at 200-300°C, and keeping the temperature for 0.5-3 hours; S5: annealing the cold-sintered sample at a temperature ranging from 650 to 800° C. for a holding time of 4 to 10 h, and finally obtaining a ZnO-based varistor ceramic.

2. The method for preparing ZnO-based varistor ceramics by annealing enhanced low temperature sintering according to claim 1, characterized in that: The metal oxide dopant is one or more of Bi2O3, Co2O3, Cr2O3, and Y2O3.

3. The method for preparing ZnO-based varistor ceramics by annealing enhanced low temperature sintering according to claim 2, characterized in that: When the metal oxide dopant consists of a plurality of metal oxides, each metal oxide accounts for 0.3-3 wt % of the total mass of the initial ZnO powder.

4. A ZnO-based varistor ceramic, characterized in that: The ZnO-based varistor is prepared by any one of the methods of claims 1-3.

Citation Information

Patent Citations

  • Ultrahigh-potential-gradient ZnO voltage-sensitive ceramic and low-carbon sintering preparation process thereof

    CN115385682A